Female Reproductive Factors and Differentiated Thyroid Cancer - Moleti, Mariacarla; Sturniolo, Giacomo; Di Mauro, Maria; Russo, Marco; Vermiglio, Francesco (Frontiers in Endocrinology, 2017)
Differentiated thyroid cancer (DTC) is markedly more common in women than men, the highest female-to-male ratio being recorded during the reproductive period. This evidence has led to the suggestion that female hormonal and reproductive factors may account for the observed DTC gender disparity. This review focuses on current evidence on the risk of DTC in conjunction with major female reproductive factors, including the impact of pregnancy on DTC occurrence and progression/recurrence. Overall, studies exploring the link between the risk of DTC and menstrual and menopausal factors, oral contraceptives and/or hormone replacement therapy, showed these associations, if any, to be generally weak. Nonetheless, there is some evidence that higher levels of exposure to estrogens during reproductive years may confer an increased risk of DTC. As far as pregnancy is concerned, it is unclear whether a potential association between parity and risk of DTC actually exists, and whether it is enhanced in the short-term following delivery. A possible role for pregnancy-related factors in DTC progression has been recently suggested by some reports, the results of which are consistent with a worse outcome in the short-term of women diagnosed with DTC during gestation compared to nonpregnant control patients. Also, some progression of disease has been described in women with structural evidence of disease prior to pregnancy. However, there seems to be no impact from pregnancy in DTC-related death or overall survival. Several in vitro and animal studies have evaluated the influence of estrogens (E) and estrogen-receptors (ER) on thyroid cell proliferation. Presently available data are indicative of a role of E and ERs in thyroid cancer growth, although considerable discrepancies in respect to ER expression patterns in thyroid cancer tissues actually exist. Further studies providing more direct evidence on the possible role of E and of placental hormones and growth factors on thyroid growth may expand our knowledge on the mechanisms beyond the gender disparity of proliferative thyroid diseases.